Buying Behaviour of Organic Food Consumers - R. A. P. I. S. Dharmadasa; M. A. E. K. Jayasinghe (Kelaniya Journal of Management)
The Theory of Planned Behavior (TPB) offers a powerful lens for understanding what drives people to choose organic food. It highlights how personal attitudes, social influences, and a sense of control over the decision all play a role in shaping buying behavior while environmental concern, price and unique qualities of organic foods, and health consciousness all play a major role in switching consumers into organic food consumption. To gain meaningful insights into key factors shaping consumers' intentions to purchase organic food, a cross-sectional survey involving 120 organic food consumers in the Colombo District was conducted using a convenience sampling approach. In identifying patterns and relationships that influence purchasing decisions, gathered data were analyzed through Pearson Correlation and Multiple Linear Regression techniques. The study finds that several psychological and product-related factors play a crucial role in shaping consumers' intentions to purchase organic food. Specifically, personal attitudes, social influences (subjective norms), a sense of control over the decision, and the inherent qualities of organic food significantly drive purchasing intentions. However, considerations such as health consciousness, environmental concerns, and price of organic food did not show a meaningful impact on consumers’ decisions to buy organic products.